Diagnosis and Treatment of Rheumatic Adverse Events Related to Immune Checkpoint Inhibitors - Yan Xiao; Lin Zeng; Qinglin Shen; Zhiyong Zhou; Zhifang Mao; Qin Wang; Xiquan Zhang; Yingliang Li; Weirong Yao (Journal of Immunology Research)
Immune checkpoint inhibitors (ICIs) have completely changed the treatment of cancer, and they also can cause multiple organ immune-related adverse reactions (irAEs). Among them, rheumatic irAE is less common, mainly including inflammatory arthritis, rheumatic myalgia/giant cell arteritis, inflammatory myopathy, and Sjogren’s syndrome. For oncologists, rheumatism is a relatively new field, and early diagnosis and treatment is very important, and we need to work closely with experienced rheumatologists. In this review, we focused on the incidence, clinical characteristics, and treatment strategies of rheumatic irAE.